Complete mitochondrial genome of the sharp-snouted pitviper Deinagkistrodon acutus (Reptilia, Viperidae) - De-Qing Wang; Li-Li Pan; Dian-Cheng Yang; Liang-Liang Dai (Mitochondrial DNA. Part B. Resources, 2019)
The sharp-snouted pitviper, Deinagkistrodon acutus, belongs to the monotypic genus Deinagkistrodon of the family Viperidae. It is one of the important species of snakes for its commercial and medicinal value. Complete mitochondrial genome sequence of the D. acutus was sequenced by next-generation sequencing technology. The total mitochondrial genome is 17,538 bp in length, containing 13 protein-coding genes, 22 tRNA genes, 2 ribosome RNA genes, and 2 control regions. Most of the genes of D. acutus are encoded on the H-strand, except for the ND6 subunit gene and eight tRNA genes which distribute on the L-strand. Phylogenetic reconstruction result indicated that our newly determined mitochondrial genome sequence could meet the demands. The complete mitochondrial genome sequence presented here will be useful to study the evolutionary relationships and genetic diversity of D. acutus.